Discovery of indane propanamides as potent and selective TRPV1 antagonists. Issue 3 (1st February 2020) - Ahn, Songyeon; Kim, Yong Soo; Kim, Myeong Seup; Ann, Jihyae; Ha, Heejin; Yoo, Young Dong; Kim, Young Ho; Blumberg, Peter M.; Frank-Foltyn, Robert; Bahrenberg, Gregor; Stockhausen, Hannelore; Christoph, Thomas; et al.
Graphical abstract: Abstract: A series of indane-type acetamide and propanamide analogues were investigated as TRPV1 antagonists. The analysis of structure–activity relationship indicated that indane A-region analogues exhibited better antagonism than did the corresponding 2, 3-dihydrobenzofuran and 1, 3-benzodioxole surrogates. Among them, antagonist 36 exhibited potent and selective antagonism toward capsaicin for h TRPV1 and m TRPV1. Further, in vivo studies indicated that antagonist 36 showed excellent analgesic activity in both phases of the formalin mouse pain model and inhibited the pain behavior completely at a dose of 1 mg/kg in the 2nd phase.